Study on the Laboratory Mixing and Compaction Methodology of Emulsified Asphalt Cold Recycled Mixture - Liu, Liping; Han, Zhanchuang; Wu, Ping; Zheng, Guangshun; Sun, Lijun (Frontiers in Materials, 2020)
Emulsified asphalt cold recycled mixture is commonly used in the upper base course of expressway reconstruction asphalt pavement. When the following layer is paved with hot-mix asphalt (HMA) mixture, the aging asphalt in the recycled material is activated due to the temperature conduction effect of the HMA mixture, so that the cold recycled layer produces “secondary thermal compaction” under the action of a roller. Based on this phenomenon, the present study aimed to discuss the influence of different molding methods and mixing processes on the volume parameters and mechanical properties of cold recycled emulsified asphalt mixture. The influences of Marshall compaction times, gyratory compaction times, curing time, and specimen-forming temperature on the voids and splitting strength of cold recycled mixture were studied. Compared with the field core sample, the laboratory-forming method, which accords with the field compaction condition of the cold recycled upper base, is recommended, that is, first-time compaction number of small Marshall is 100 times and secondary thermal compaction number is 50 times (previous research)（Shorthand for 100+50）, the compaction times of large Marshall specimen is “150 + 75”, gyratory specimen is “30+15”. The curing time of cold recycled mixture should not exceed 3 h and should not be constructed in low-temperature weather to ensure the quality of pavement construction. The use of a new stage and step laboratory mixing process simulating the plant mixing, compared with the traditional mixing process, increases the splitting strength by at least 13%.